MOTIVASI PEMERINTAH SKOTLANDIA MELAKUKAN REFERENDUM SEBAGAI UPAYA PEMISAHAN DIRI DARI BRITANIA RAYA PADA TAHUN 2014 - Putra, Rinaldo Dwi; Tjarsono, Idjang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research describes about the motivation of the Scottish Government for a referendum as an attempt secession from the United Kingdom in 2014. The United Kingdom are a combination of England, Scotland, Wales, and Northern Ireland. Scotland?s area are 78.772 km2 or covers one-third of the United Kingdom. The Scottish government have different views and ideas with the British Government on policy making in some sectors. Scotland also has a great potential in the oil and gas resources that should be able to support the national economy.This research using qualitative method that collect data related from various sources. The writer collects data from books, encyclopedia, journals, mass media, and websites to analyze about motivation of Scottish Government conduct a referendum on independence. The theory applied in this research is the perspective of realism to the theory of ?public policy? by William N. Dunn.The results of this research shows that the Scottish Government's ambition to make Scotland a more democratic, build more prosperous country, and realize a more equitable society. Scotland?s Referendum was held on September 18, 2014, with the result that 55.25 percent of the people of Scotland choose to still be a part of the United Kingdom and 44.65 percent choose independence.Key words: referendum, public policy, national economy